Pengaruh Layanan Penguasaan Konten untuk Memperbaiki Komunikasi Verbal Siswa: Pengaruh Layanan Penguasaan Konten untuk Memperbaiki Komunikasi Verbal Siswa - Atika Desya Ifanda; Rita Sinthia; MT Afriwilda (UNIVERSITAS BENGKULU, 2024)
The research aims to describe the influence of content mastery services to improve students' verbal communication.. The design of this research is experimental. The pre-test results show that students in the high category have a percentage of 26.67%. The verbal communication students in the content mastery service pre-test was on average in the low category with a sample of 30 students. The technique used in this research is a verbal communication questionnaire with a Likert scale, given to students via pre-test and post-test. The post-test results show that students in the high category have a percentage of 36.67%. Based on the research conducted, content mastery services to improve verbal communication provide positive things, apart from being seen from the results of the pre-test and post-test that have been given which show an improvement, the provision of content mastery services help students understand verbal communication so that students are able to study words or sentences well. Keywords: content mastery services, verbal communication, students